Lower limb asymmetry after anterior cruciate ligament reconstruction in adolescent athletes: A systematic review and meta-analysis - Hughes, G.; Musco, P.; Caine, S.; Howe, L. (Journal of Athletic Training, 2020)
Objectives: To identify reported (1) common biomechanical asymmetries in the literature after anterior cruciate ligament (ACL) reconstruction in adolescents during landing and (2) timescales for asymmetry to persist postsurgery. Data Sources: We identified sources by searching the CINAHL, PubMed, Scopus, and SPORTDiscus electronic databases using the following search terms: asymmetry OR symmetry AND landing AND biomechanics OR kinematics OR kinetics. Study Selection: We screened the titles and abstracts of 85 articles using our inclusion criteria. A total of 13 articles were selected for further analysis. Data Extraction: Three reviewers independently assessed the methodologic quality of each study. We extracted the effect sizes directly from studies or calculated them for biomechanical variables assessing asymmetry between limbs of participants with ACL reconstruction. We conducted meta-analyses on variables that were assessed in multiple studies for both double- and single-limb landings. Data Synthesis: Asymmetry was more commonly identified in kinetic than kinematic variables. Anterior cruciate ligament reconstruction appeared to have a large effect on asymmetry between limbs for peak vertical ground reaction force, peak knee-extension moment, and loading rate during double-limb landings, as well as mean knee-extension moment and knee energy absorption during both double- and single-limb landings. Conclusions: Our findings suggested that return-to-sport criteria after ACL reconstruction should incorporate analysis of the asymmetry in loading experienced by each limb rather than movement patterns alone.